Mothers, babies, and abortion at the border: Contradictory U.S. policies, or targeting fertility?. (December 2021) - Hiemstra, Nancy
Migrant women's fertility—or more precisely, non-white migrant women's fertility—has long been the subject of fear and anger in the United States. This negativity is evident in attitudes, discourse, and policies around immigration, as seen in terms such as "anchor baby, " debates over birthright citizenship, and caricatured ideas of migrant women's reproduction and sexuality. In 2018, the Trump administration put in place a number of policies targeting migrant fertility in various ways, among them family separation at the U.S.-Mexico border, and the denial of abortions to detained immigrant teens. This article explores the apparent contradiction of ripping immigrant families apart, while at the same time essentially forcing the production of new non-white citizens. Drawing on feminist geographic and queer studies theoretical lenses, the article identifies three fertile figures constructed in contemporary discourse around immigration: the breeder, the anchor baby, and the bad parent. This approach provides a window into the enduring white, patriarchal, heteronormative nationalism particularly evident at this point in U.S. history. It also illuminates ways in which these policies collectively work to erase the United States' colonial past and present, and the centrality of racial hierarchies to contemporary global capitalism.